Thyroid hormones and their placental deiodination in normal and pre-eclamptic pregnancy - Kurlak, L.O.; Mistry, H.D.; Kaptein, E.; Visser, T.J.; Broughton Pipkin, F. (Placenta (Eastbourne), 2013)
Pre-eclampsia is associated with lower serum selenium concentrations and glutathione peroxidase expression/activity; total thyroid hormones are also lower. We hypothesised that the placental selenoprotein deiodinase (D3) will be protected in pre-eclampsia due to the hierarchy of selenoprotein biosynthesis in selenium deficiency. Venous blood and tissue from three standardised placental sites were obtained at delivery from 27 normotensive and 23 pre-eclamptic women. mRNA expression and enzyme activity were assessed for both deiodinases (D2 and D3); protein expression/localisation was also measured for D3. FT4, FT3 and TSH concentrations were measured in maternal and umbilical cord blood. No significant differences in D3 mRNA or protein expression between normotensive and pre-eclamptic pregnancies. There was a significant effect of sampling site on placental D3 activity only in pre-eclamptic women (P = 0.034; highest activity nearest the cord). A strong correlation between D3 mRNA expression and enzyme activity existed only in the pre-eclamptic group; further strengthened when controlling for maternal selenium (P < 0.002). No significant differences were observed between groups for any of the maternal thyroid hormones; umbilical TSH concentrations were significantly higher in the pre-eclamptic samples (P < 0.001). D3 mRNA and protein expression appear to be independent of selenium status. Nevertheless, the positive correlation between D3 mRNA expression and activity evident only in pre-eclampsia, suggests that in normotensive controls, where selenium is higher, translation is not affected, but in pre-eclampsia, where selenium is low, enzyme regulation may be altered. The raised umbilical TSH concentrations in pre-eclampsia may be an adaptive fetal response to maximise iodide uptake.